2022
DOI: 10.1111/pbi.13826
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin integrates cellular energetics and cell cycle to regulate maize seed development

Abstract: Summary Riboflavin is the precursor of essential cofactors for diverse metabolic processes. Unlike animals, plants can de novo produce riboflavin through an ancestrally conserved pathway, like bacteria and fungi. However, the mechanism by which riboflavin regulates seed development is poorly understood. Here, we report a novel maize (Zea mays L.) opaque mutant o18, which displays an increase in lysine accumulation, but impaired endosperm filling and embryo development. O18 encodes a rate‐limiting bifunctional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…Consistent with the loss of complex I NADH dehydrogenase activity, the NADH/NAD + ratio was higher in crk1-1, consequently resulting in a decrease in ATP abundance (Figure 4H). This scenario is exactly in line with that observed for the maize o18 mutant, which also has defects in complex I function (Tian et al, 2022).…”
Section: Loss Of Function Of Zndufaf1 Leads To Changes In Cellular En...supporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the loss of complex I NADH dehydrogenase activity, the NADH/NAD + ratio was higher in crk1-1, consequently resulting in a decrease in ATP abundance (Figure 4H). This scenario is exactly in line with that observed for the maize o18 mutant, which also has defects in complex I function (Tian et al, 2022).…”
Section: Loss Of Function Of Zndufaf1 Leads To Changes In Cellular En...supporting
confidence: 88%
“…In humans, complex I dysfunction is responsible for around one-third of mitochondrial diseases, such as Leigh syndrome, lactic acidosis, leukoencephalopathy, and isolated myopathy (Ghezzi and Zeviani, 2018). In contrast, plants lacking complex I exhibit growth and development retardation and/or, commonly, seed abortion (Wang et al, 2017;Ligas et al, 2019;Tian et al, 2022). Nonetheless, some unicellular and multicellular organisms naturally lack complex I but compensate through diverse mechanisms, such as the acquisition of ATP from host cells, degeneration or rearrangement of the respiratory chain, or alternative oxidoreduction (Mayer and Muller, 2014;Raven and Beardall, 2017;Maclean et al, 2018;Senkler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A well-known example is the progressive repression of FLOWERING LOCUS C (FLC) by H3K27me3 during vernalization 49 . Studies in rice and maize have reported the role of histone modifications in endosperm starch and protein accumulation [24][25][26][27][28] . We mapped H3K27me3, H3K4me3 and H3K9ac in wheat endosperm to explore the role of histone modifications on gene transcription during endosperm development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a large number of genes involved in nutrient metabolic pathway are directly regulated in the endosperm by OsFIE2-catalyzed H3K27me3. Up-regulation of cell cyclerelated genes in maize opaque mutant opaque18 correlates with increased levels of H3K4me3 28 . Moreover, a majority number of paternally expressed imprinted genes and transposable elements are marked by H3K27me3 in maize and Arabisopsis endosperm [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation